Nested Dependency: President Joko Widodo’s Politics Strategy in Coopting Nahdlatul Ulama, 2014-2024 - Faiz Ali Ba'agil; Achmad Ubaedillah; Savran Billahi (Universitas Islam Internasional Indonesia (UIII), 2026)
This article analyzes Joko Widodo (Jokowi)’s systematic strategy to incorporate Nahdlatul Ulama (NU)—Indonesia’s largest Islamic organization—into his efforts to ensure the stability of his presidency (2014–2024). Using Johannes Gerschewski’s three-pillar framework of autocratic stability—legitimation, repression, and co-optation—adapted to Indonesia’s democratic backsliding, this qualitative case study combines critical discourse analysis of presidential speeches and NU documents, process tracing of key political events, and interviews with two key informants familiar with NU–state relations. The findings identify three interconnected mechanisms. First, Jokowi used NU as a source of legitimacy by securing its institutional endorsement and framing NU as the embodiment of “moderate Islam,” encouraging grassroots political passivity. Second, NU functioned as a tool of symbolic repression against opposition Islamic groups—FPI, HTI, and the 212 movement—through the reinforcement of the moderate–radical dichotomy, delegitimizing dissent without direct coercion. Third, Jokowi co-opted NU elites through political appointments and economic enticements—including a 26,000-hectare coal mining concession and intervention in NU’s 2021 leadership contest—creating what this study terms “nested dependency,” a multilayered form of dependence linking elite, organizational, and grassroots levels. However, interview findings reveal that this dependency was temporally limited by presidential incumbency. As an institutionally pragmatic rather than patron-dependent organization, NU shifted its alignment toward President Prabowo after Jokowi’s departure, confirming that NU ultimately follows the presidency as an institution rather than any individual patron. This study contributes to debates on democratic backsliding and state–civil society relations in Southeast Asia.